1991
DOI: 10.1007/bf01024786
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, immunochemical, and thermodynamic properties of carboxymethyl(Cys6, Cys127)-hen egg white lysozyme

Abstract: A three-disulfide form of hen egg white lysozyme with Cys6 and Cys127 blocked by carboxymethyl groups was prepared, purified, and characterized for eventual use in protein folding experiments. Trypsin digestion followed by proline-specific endopeptidase digestion facilitated the unambiguous assignment of the disulfide bond pairings and the modified residues in this derivative. 3SS-lysozyme demonstrated nearly full enzymatic activity at its pH optimum, pH 5.5. The 3SS-lysozyme derivative and unmodified lysozyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…The 'H NMR spectra of lysozyme and CM6'127-lysozyme have been completely assigned at 35 °C and pH 3.8 (Redfield & Dobson, 1988;Radford etal., 1991). Both proteins are native under these conditions with virtually identical structures, as judged by NMR and X-ray crystallography (Radford et al, 1991;Hill et al, 1993) and by optical methods (Denton & Scheraga, 1991); indeed, the three-disulfide derivative largely retains its enzymatic activity (Radford et al, 1991). At this temperature, however, although CM6-127-lysozyme is still folded, the majority of backbone amides exchange, some to a substantial degree, with bulk solvent during the 4 h acquisition time of a COSY experiment, whereas amides in the unmodified protein are stable against exchange for weeks under these conditions (Pedersen et al, 1991).…”
Section: Resultsmentioning
confidence: 98%
“…The 'H NMR spectra of lysozyme and CM6'127-lysozyme have been completely assigned at 35 °C and pH 3.8 (Redfield & Dobson, 1988;Radford etal., 1991). Both proteins are native under these conditions with virtually identical structures, as judged by NMR and X-ray crystallography (Radford et al, 1991;Hill et al, 1993) and by optical methods (Denton & Scheraga, 1991); indeed, the three-disulfide derivative largely retains its enzymatic activity (Radford et al, 1991). At this temperature, however, although CM6-127-lysozyme is still folded, the majority of backbone amides exchange, some to a substantial degree, with bulk solvent during the 4 h acquisition time of a COSY experiment, whereas amides in the unmodified protein are stable against exchange for weeks under these conditions (Pedersen et al, 1991).…”
Section: Resultsmentioning
confidence: 98%
“…The 6,127-rcm derivative of lysozyme is thermodynamically less stable than unmodified lysozyme (18,19), which might suggest that it is the unfolded protein that is recognized by the Ub-protein ligase, E3a. We have found that this is not the case.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional NMR measurements by Radford et al (18) support our conclusion that the N-terminal portion of 6,127-rcm-lysozyme is virtually the same as that of the native protein. From an immunochemical study, however, it appeared that the 6,127-rcmlysozyme N-terminal region may be distorted relative to the native conformation (19). The immunochemical and structural data can be reconciled if the N-terminal epitopes that were probed also included Cys-6 or distal portions of the antigen such as its C terminus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disulfide bonds can make a substantial contribution to protein stability. The effect of disulfide bonds on stability has been studied in many small globular proteins, such as ribonuclease (Pace et al 1988) and lysozyme (Matsumura et al 1989; Denton and Scheraga 1991; Taniyama et al 1992). For antibodies, the effect of a disulfide bond on stability has been investigated using various isolated domains (Goto and Hamaguchi 1979; Glockshuber et al 1992; Proba et al 1997; Thies et al 2002).…”
mentioning
confidence: 99%